2021
DOI: 10.1038/s41419-021-04370-8
|View full text |Cite
|
Sign up to set email alerts
|

MRPS31 loss is a key driver of mitochondrial deregulation and hepatocellular carcinoma aggressiveness

Abstract: Deregulated mitochondrial energetics is a metabolic hallmark of cancer cells. However, the causative mechanism of the bioenergetic deregulation is not clear. In this study, we show that somatic copy number alteration (SCNA) of mitoribosomal protein (MRP) genes is a key mechanism of bioenergetic deregulation in hepatocellular carcinoma (HCC). Association analysis between the genomic and transcriptomic profiles of 82 MRPs using The Cancer Genome Atlas-Liver HCC database identified eight key SCNA-dependent MRPs: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…This may regulate the expression of corresponding genes through their negatively related promoter methylation to adapt to the wildness training process. NME7 gene knockdown causes primary ciliary dyskinesia ( Šedová et al, 2021 ), MRPS31 gene deletion causes mitochondrial deregulation and the aggression of hepatocellular carcinoma ( Min et al, 2021 ), and TPM1 gene knockdown causes early embryonic death ( Ma et al, 2021 ). The deletion or low expression of these genes above can cause disease development.…”
Section: Discussionmentioning
confidence: 99%
“…This may regulate the expression of corresponding genes through their negatively related promoter methylation to adapt to the wildness training process. NME7 gene knockdown causes primary ciliary dyskinesia ( Šedová et al, 2021 ), MRPS31 gene deletion causes mitochondrial deregulation and the aggression of hepatocellular carcinoma ( Min et al, 2021 ), and TPM1 gene knockdown causes early embryonic death ( Ma et al, 2021 ). The deletion or low expression of these genes above can cause disease development.…”
Section: Discussionmentioning
confidence: 99%
“…In the broader literature, Min's research proposed MRPS31 as an emergent biomarker for HCC, and Foo's work underscored the pivotal role of CYCS in driving apoptotic processes within HCC cells. 33,34 To validate the prognostic robustness of these identified genes, we segregated patients from the TCGA cohort into high-risk and low-risk categories based on their median risk scores. Kaplan-Meier survival curves painted a clear dichotomy in the prognoses between these groups.…”
Section: Discussionmentioning
confidence: 99%
“…Through the COX survival analysis of DEGs using the tinyarray package, we identified five genes—MRPL15, CYCS, MRPS35, NDFIP1, and ATP6V1G1—as having significant prognostic implications. In the broader literature, Min's research proposed MRPS31 as an emergent biomarker for HCC, and Foo's work underscored the pivotal role of CYCS in driving apoptotic processes within HCC cells 33,34 . To validate the prognostic robustness of these identified genes, we segregated patients from the TCGA cohort into high‐risk and low‐risk categories based on their median risk scores.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the functional enrichment analysis of the m7G-related genes with GO revealed that some of them were associated with the pathogenesis of HCC. Mitochondrial dysregulation is associated with the aggressiveness of HCC ( Min et al, 2021 ). Actin−mediated cellular activity is associated with cell migration and invasion, which may play important role in the development of cancer ( Guan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%